IMPROVING STUDENTS’ DIGITAL LITERACY THROUGH THE RELIGIOUS CHARACTER IN MTS NEGERI 1 SIDRAP - St Aflahah (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
Students’ digital literacy has become crucial in society 5.0, but it also brings negative effects on students’ development. Character education comes to reduce the drawbacks of using technology, particularly the religious character. MTSN 1 Sidrap was selected as it develops students’ digital literacy through the integration of e-learning Madrasah and Google Meet. It also supports students’ religious character since it is a Madrasah, offering more religious subjects than junior high schools. This study used qualitative research with a semi-structured interview to obtain in-depth data. The participants in this research were three teachers. They were one female Mathematics teacher who is also an ICT (Information and Communication Technology) teacher and two male Islamic teachers. This study found that students’ digital literacy has met the standards required by the curriculum. However, students’ digital culture and ethics need more attention since students have an opportunity to access inappropriate content and plagiarism. The religious character could overcome such issues by implementing religious dimensions, particularly religious belief, ritual, devotion, experience, and knowledge. Moreover, the dimension of religious ritual reveals that although students practice the pillars of Islam, it does not practically make students stop doing things that are forbidden by the Islamic religion. Hence, the indicators of students’ religious character in the curriculum that focuses on students’ religious rituals or practices are inadequate. The dimensions of religious devotion and experience are crucial in describing students’ attachment to Allah, which can increase students’ awareness to avoid behaviors that violate Islamic teachings.